Promoting Learning Amidst Pandemic : A Thematic Content Analysis on the Curriculum Management Aspect of DepEd’s Basic Education Learning Continuity Plan (BE-LCP) - Manire, Rocky Niño (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2021)
The COVID-19 pandemic has disrupted the basic education system in the Philippines. As a response, the Department of Education devised a Learning Continuity Plan to carry on with the learning process. This paper deals with the uncovering of the curriculum management aspect of the Department of Education of the Philippines’ BE-LCP through thematic content analysis. Findings revealed the four phases of the curriculum management of BE-LCP anchored in the adjustments made in the aspects of learning; these are: 1) Correcting Phase (Learning Content); 2) Connecting Phase (Learning Delivery); 3) Coping Phase (Learning Management), and 4) Collecting Phase (Learning Assessment). Further empirical research on the impact of the BE-LCP implementation in Public Basic Education Institutions across the Philippines is recommended.